Proposal of Design Formulae for Equivalent Elasticity of Masonry Structures Made with Bricks of Low Modulus - Muhammad Ridwan; Isamu Yoshitake; Ayman Y. Nassif (Advances in Civil Engineering)
Bricks of low elastic modulus are occasionally used in some developing countries, such as Indonesia and India. Most of the previous research efforts focused on masonry structures built with bricks of considerably high elastic modulus. The objective of this study is to quantify the equivalent elastic modulus of lower-stiffness masonry structures, when the mortar has a higher modulus of elasticity than the bricks, by employing finite element (FE) simulations and adopting the homogenization technique. The reported numerical simulations adopted the two-dimensional representative volume elements (RVEs) using quadrilateral elements with four nodes. The equivalent elastic moduli of composite elements with various bricks and mortar were quantified. The numerically estimated equivalent elastic moduli from the FE simulations were verified using previously established test data. Hence, a new simplified formula for the calculation of the equivalent modulus of elasticity of such masonry structures is proposed in the present study.